KAJIAN RHODAMIN B, KUALITAS MIKROBIOLOGI DAN SANITASI PADA JAJANAN KAKI LIMA SEKITAR SEKOLAH DASAR DI SAMARINDA, INDONESIA [ASSESSMENT OF RHODAMINE B, MICROBIOLOGICAL QUALITY AND SANITATION OF STREET-VENDED FOOD-SNACK AROUND SCHOOL IN SAMARINDA] - Krishna Purnawan Candra; Ratna Setia Ningsih; Sukmiyati Agustin; Elisa Maulidya Putri (Persagi, 2019)
The incidence of foodborne disease caused by street food in Indonesia tends to increase. Meatball served with tomato sauce is popular among elementary school students in Indonesia. This research examined the safety of the sauce used for meatball sold among the elementary school students in Samarinda. Rhodamine B and microbiological quality of the tomato sauce were examined from 25 vendors. Sanitation during the meatball preparation by each vendor was also questioned. Results showed that 79.2% of the vendor sold the meatball with Rhodamine B was positively detected in the tomato sauce. All sauce did not meet the requirements of the microbiological quality of Indonesian standard. It might be caused by cross-contamination of the pathogenic microbes from equipment, poor vendor sanitation while preserving the sauce, or the water used in the preserving processed. Contamination from air pollution also needs serious attention because the vendors sold the meatball in the street or by the roadside.